Early Life Impacts on Later Life Health and Economic Outcomes - Diane Whitmore Schanzenbach (Washington University Journal of Law & Policy, 2018)
In this article, Diane Whitmore Schanzenbach explores how access to the Supplemental Nutrition Assistance Program (SNAP) not only contributes to better health outcomes for children, but also better health and economic outcomes later in life. Notably, Schanzenbach finds that these impacts are greater when SNAP is available during the in-utero period of childhood development and taper off when introduced at later stages – indicating that SNAP may be having an impact on childhood brain development. Schanzenbach points to the broader implications of these findings by asserting that early childhood investment has a more significant long-term economic impact than is currently understood and that policy makers should look at intervention programs as economic investments and not solely as charity.
Keywords: Supplemental Nutrition Assistance Program; intervention programs; social safety net; childhood development; poverty; food insecurity; economic outcomes; health outcomes; self-sufficiency.